Bacterial Inoculants Mitigating Water Scarcity in Tomato: The Importance of Long-Term in vivo Experiments - Riva, Valentina; Mapelli, Francesca; Dragonetti, Giovanna; Elfahl, Mustafa; Vergani, Lorenzo; Crepaldi, Paola; La Maddalena, Nicola; Borin, Sara (Frontiers in Microbiology, 2021)
Global population growth and climate change raise a challenge to agriculture which, combined with the issues concerning the use of chemical fertilizers, have generated increasing attention in the use of plant-associated bacteria as a sustainable strategy in the agri-food systems. The objective of this study is to evaluate the ability of five bacterial strains, previously isolated from the rhizosphere or endosphere of plants adapted to harsh environmental conditions, to act as potential plant biofertilizers in different conditions of water availability. The strain biosafety for a deliberate environmental release was investigated through literature survey and antibiotic resistance testing. The selected strains were firstly characterized for their plant growth-promoting (PGP) and rhizocompetence-related traits through in vitro assays and then on short-term in vivo experiments on tomato plants. A long-term greenhouse experiment was further conducted to monitor the PGP effect of the bacteria during the entire life cycle of tomato plants subjected to full irrigation or to severe water deficit conditions, aiming to assess their actual effect on plant productivity, which is the ultimate target of the agricultural sector. Some of the strains showed a potential in improving water use efficiency and mitigating plant water stress. Under severe irrigation deficit, four of the tested strains, Micrococcus yunnanensis M1, Bacillus simplex RP-26, Pseudomonas stutzeri SR7-77 and Paenarthrobacter nitroguajacolicus 2-50, significantly increased the number of productive plants in comparison to non bacterized control ones. Two of them, Bacillus simplex RP-26 and Paenarthrobacter nitroguajacolicus 2-50, demonstrated also, under full irrigation, to significantly improve the water productivity in comparison with non bacterized plants. Despite all the strains showed promising PGP potential in short-term assays, the positive effect of the bacterial inoculants on plant physiology and fruit yield was observed in some cases, but never corroborated by statistical significance. These results highlighted the importance of performing long-term in vivo experiments to define the real PGP ability of a bacterial inoculant to positively impact plant production.